2017
DOI: 10.1177/0886260517744190
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Sexual Victimization Estimates to Definitional and Measurement Decisions

Abstract: Self-report surveys are subject to measurement error associated with variation in the methodology employed. The current analysis uses data from the Campus Climate Survey Validation Study (CCSVS) to examine the impact that measurement decisions have on estimates. The findings demonstrate that asking victims to provide detailed information in an effort to properly place incidents in time and classify incidents by type resulted in relatively minor decreases in estimate magnitude. Ultimately, asking respondents to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
(27 reference statements)
2
25
0
Order By: Relevance
“…The study findings are likely generalizable to any North American university campus, particularly because our sample across three universities of different sizes and characteristics was more demographically diverse than the samples represented in most intervention research in this field (for an exception, see Krebs et al, 2016). We do not know whether EAAA would have similar effects for less privileged young women who do not attend university, although we have some preliminary data suggesting it may be appropriate for younger girls (Senn, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study findings are likely generalizable to any North American university campus, particularly because our sample across three universities of different sizes and characteristics was more demographically diverse than the samples represented in most intervention research in this field (for an exception, see Krebs et al, 2016). We do not know whether EAAA would have similar effects for less privileged young women who do not attend university, although we have some preliminary data suggesting it may be appropriate for younger girls (Senn, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The alarming rates of campus sexual assault were first documented nearly 30 years ago (in Canada: DeKeseredy & Kelly, 1993; in the United States: Koss, Gidycz, & Wisniewski, 1987), and these rates have not changed (e.g., Fisher, Cullen, & Turner, 2000; Krebs et al, 2016; Krebs, Lindquist, Warner, Fisher, & Martin, 2009). Male acquaintances perpetrate the vast majority of these attacks.…”
mentioning
confidence: 99%
“…This questionnaire included cues regarding sexual behavior (e.g., I put my penis in someone's vagina) as well as sexual tactics (e.g., I used physical force: Krahé et al, 2016;Krahé & Vanwesenbeeck, 2015). For more on one-stage vs. two-stage strategies see Krebs et al, 2017. Also supporting the hypothesis that the findings of Krebs et al (2007) could be an underestimate, Strang and Peterson (2017)'s work demonstrated that unintentional underreporting related to misinterpretation of items is as likely a source of error as intentional underreporting. In other words, respondents are equally likely to underreport because they do not understand an item as they are to underreport because they want to provide a socially desirable response.…”
Section: Prevalence Of Sexual Violence Perpetrationmentioning
confidence: 99%
“…As noted by Muehlenhard et al (2017), recent multicampus climate surveys have demonstrated dramatic differences in prevalence rates between institutions. In two such studies conducted by the American Association of Universities (Cantor, Fisher, & Chibnall, 2015) and the Bureau of Justice Statistics (C. Krebs et al, 2016), prevalence rates ranged from 13% to 30% and from 4.2% to 20%, respectively, between campuses.…”
mentioning
confidence: 99%